2003
DOI: 10.1038/sj.leu.2402766
|View full text |Cite
|
Sign up to set email alerts
|

New mechanisms of AML1 gene alteration in hematological malignancies

Abstract: The human AML1 gene (also named CBFA2 or RUNX1), located in the 21q22 chromosomal band, encodes for one of the two subunits forming a heterodimeric transcription factor, the human core binding factor (CBF). AML1 protein contains a highly evolutionary conserved domain of 128 amino acids called runt domain, responsible for both heterodimerization with the ␤ subunit of CBF and for DNA binding. AML1 is normally expressed in all hematopoietic lineages and acts to regulate the expression of various genes specific to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
104
0
10

Year Published

2004
2004
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 125 publications
(117 citation statements)
references
References 39 publications
3
104
0
10
Order By: Relevance
“…The reported amplifications hot spots harbor such amplification-activated oncogenes as EGFR, MYCN, MYC and ERBB2 (Futreal et al, 2004) ( Table 1). The RUNX1 (alias AML1) gene amplification (gene locus 21q22.3 maps to amplification hot spot 27) is typical in a variety of hematologic malignancies (Roumier et al, 2003). 11q23-qter is typically amplified in AML but rarely in other tumors (Zatkova et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The reported amplifications hot spots harbor such amplification-activated oncogenes as EGFR, MYCN, MYC and ERBB2 (Futreal et al, 2004) ( Table 1). The RUNX1 (alias AML1) gene amplification (gene locus 21q22.3 maps to amplification hot spot 27) is typical in a variety of hematologic malignancies (Roumier et al, 2003). 11q23-qter is typically amplified in AML but rarely in other tumors (Zatkova et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…125,128 Acquired AML1 mutations observed in other FAB subtypes are often monoallelic and often associated with acquired trisomy 21 or other cytogenetic abnormalities, such as trisomy 13, or with FLT3, P53 or N-RAS mutations. 133,134 Interestingly, in patients with constitutional trisomy 21 (that is, Down syndrome), who have a propensity to develop AML, no AML1 mutations have been found. Copy number variation of the AML1 gene could be presompted to participate to leukemogenesis both by increase or defect.…”
Section: Aml1mentioning
confidence: 99%
“…It has previously been reported that biallelic mutations of another early myeloid differentiation gene (AML1/ RUNX1) could induce M0 AML subtype. 2 Furthermore, mice models of CML blast crisis with CEBPA knockout result in immature erythroid leukemia 30,31 and expression of a dominant negative 30-kDa CEBPA protein inhibits differentiation of myeloid and erythroid progenitors. 32 On the other hand, all CEBPAmutated patients reviewed in this work had M1, M2, M4 or M5 AML subtypes, clearly showing persistence of myeloid differentiation in blast cells.…”
Section: Pathogenetic Role Of Cebpa Mutationsmentioning
confidence: 99%
“…1 In acute myeloid leukemia (AML), cell differentiation arrest can occur at different levels by alteration of specific genes like those of the CBF complex. 2 The CEBPA gene (located on chromosome 19q13.1 band) belongs to the CCAAT/enhancer-binding protein family, which is involved in the balance between cell proliferation and terminal differentiation. CEBPA gene mRNA can be translated from the first AUG encoding the 42-kDa normal isoform and also from the second AUG (nt 508-510) encoding the 30-kDa normal isoform, which has lost the 119 first AA including the TAD1 functional domain.…”
Section: Introductionmentioning
confidence: 99%